Usability Guidelines for Designing Mobile Apps User Interface for Children with Autism: a Systematic Literature Review - Mohamad Sofian, Nadiah; Sobri Hashim, Ahmad; Fatimah Wan Ahmad, Wan (International Journal of Engineering and Technology, 2018)
In the recent years major advancement in technologies that support the children that have been diagnosed with the autism. The increasing number of application is to enhance their ability in communication, understanding, and interface with others. There are over 200 mobile applications for autistic children that can be found in the current market. However, these mobile applications did not use standard guidelines which cause some difficulties to use and learn by the autistic children. This is because of the lack of usability guidelines for mobile application which are relatively unexplored and unproven. There are 142 publications obtained by the automatic searched and 23 relevant studies have been selected as the primary studies. The process was achieved with manual searches using keywords and snowballing techniques to identify the usability factors. This systematic review investigates on the study of the existing usability factors that frequently have been used in designing mobile application for autistic children. It was found that understandable and appearance were included as the usability factors due to their relevancy towards the characteristics of the autistic children. The results are useful for future enhancement in this field to develop usability guideline in designing mobile application user interface in different fields.Â Â